EVALUATION OF INTEGRATED TECHNOLOGIES LEACHATE WASTE STORAGE - , М. В. (Municipal economy of cities. Series: «Economy science», 2013)
The problem of negative influence of functioning of the range of the solid domestic wastes (SDW) on environment is considered, the method of cleaning of a leachate is offered, its efficiency is estimated.